A case of nephrotic syndrome secondary to HIV immune complex kidney disease - Michael Edwards; Patrick Linden; Anindya Banerjee (Society of Diabetic Nephropathy Prevention, 2021)
HIV immune complex disease of the kidney (HIVICK) is a rare but increasingly well-recognised cause of renal dysfunction and proteinuria in HIV-positive patients. A 56-year-old man with known HIV, diabetes mellitus type 2, liver cirrhosis and previous Hepatitis C virus (HCV) presented with a labile estimated glomerular filtration rate and significant proteinuria. Electron microscopy from a renal biopsy identified capillary wall deposition for IgG, IgM, Kappa, Lambda and focal C1q consistent with membranoproliferative glomerulonephritis (MPGN) and associated immune complex disease. A second opinion of the images confirmed the diagnosis of HIVICK. The increased recognition of HIVICK in HIV patients should prompt further research into the causes and treatment options available.